PEMANFAATAN E-COMMERCE UNTUK MEMPERLUAS PASAR UMKM DI KELURAHAN GANTING KOTA PADANG PANJANG DI ERA DIGITAL - Renda Putri; Tiara Rabiatul Adhawiyyah; Nurzakiyya Nurzakiyya; Aeryn Febi Sabrina; Anisalsa Derian Hasanah; Farhan Akbar; Latifah Safitri; Muhammad Zaki; Najwa Khairunnisa; Seftia Rahma Wati; Yulia Ningsih (PUAN INDONESIA, 2026)
The rapid development of information technology in the digital economyera requires Micro, small, and medium enterprises (MSMEs)to adapt fromconventional marketing systems to digital systems to expand marketreach. However, MSMEs in Ganting Village, Padang Panjang City, still facesignificant obstacles, including low digital literacy. Limited ability to mangeonline stores on marketplaces, and a lack of skills in creating attractivemarketing content. The community service program uses a descriptivequalitative approach. The activities were conducted on December 12, 2025,targeting MSMEs actors and PKK members in Ganting Villge. Theimplementation methods included educational materials, socialization,intensive training on creating product content and digital salesmanagement. The implementation of the activities showed positive resultsin increasing the participants’ knowledge and digital literacy. Mostparticipants began to umderstand the basic steps of uploading products,writing attractive descriptions, and managing online consumercommunication. Furthermore, the program encouraged a midset shiftamong MSMEs toward adopting digital based business recording systems.